Characterization of Lactobacillus rhamnosus MP01 and Lactobacillus plantarum MP02 and Assessment of Their Potential for the Prevention of Gastrointestinal Infections in an Experimental Canine Model - Fernández, Leónides; Martínez, Raquel; Pérez, Manuela; Arroyo, Rebeca; Rodríguez, Juan M. (Frontiers in Microbiology, 2019)
The probiotic potential of Lactobacillus rhamnosus MP01 and Lactobacillus plantarum MP02, two strains isolated from canine milk, was evaluated through different assays, including survival to conditions similar to those found in the canine gastrointestinal tract, production of antimicrobial compounds, adherence to intestinal mucin, degradation of mucin, and pattern of antibiotic sensitivity. Globally, both strains showed a high in vitro probiotic potential. Subsequently, acute and repeated dosis toxicity was tested in a rat model, which confirmed the safety of the strains. Finally, a pilot clinical trial was performed to evaluate the potential of the strains to prevent episodes of infectious gastroenteritis when administered for 2 months to 1-month-old puppies. A group (n=12, 6 males and 6 females) of German shepherd puppies received L. rhamnosus MP01 while a second group (n=12, 6 males and 6 females) received L. plantarum MP02. The same trial was performed with Yorkshire puppies and one placebo group for each breed (German shepherd, n=12; Yorkshire, n=12) was also included. The results showed that administration of the strains was associated to a significant preventive effect in such populations.